Integrasi Metode Service Quality (Servqual) dan Importance Performance Analysis (IPA) Untuk Menganalisa Kualitas Pelayanan Terhadap Kepuasan Konsumen di CV. Mubarokfood Cipta Delicia - Husaeni, Alfi; Tauhida, Dina; Prayogo, Adhie; Sokhibi, Akh. (Universitas Muria Kudus, 2024)
Mubarokfood is a company producing typical food products, namely jenang and dodol. Facilitated with the modern-type market, Mubarokfood does not only eager to sell the products but also provides convenience for the customer while roaming around the showroom. Yet, the improvement process should be performed continuously. Especially after the earlier observation discovered some dissatisfactions among customers, including the lack of employee resposinveness in serving, lack of trolly. According to the mentioned dilemma, an assessment of the quality service and its improvements are required. A combination of servqual and Importance Performance Analysis (IPA) method were implemented within the study to asses the service quality level perceived by the customer. A questionnaire containing 5 dimensions, namely Tangible, Reliability, Responsiveness, Assurance and Emphaty, with detailed 25 service attributes were distributed among 100 respondents. The servqual method found out that the 5 dimensions have overall negative value while the IPA method discovered that the product placement procedure should be improved to ease the visitors, employee responsiveness improvement is required. Finally, the study suggested to initiate an intensive employee training related to the customer service and product knowledge for marketing. Also, a noticeable product label could be set on top of the layout